Khuruj as Transformational Pedagogy: The Mobilization of Da'wah and the Formation of Spiritual Capital in Jamaah Tabligh - Tohirin; Muhammad Dwi Fajri; Ali Zainal Abidin; Abdullah RS; Ati Maryati (Walidem Institute and Publishing, 2026)
Objective: This study aims to analyze the concept of khuruj in Jamaah Tabligh as a model of transformational pedagogy that shapes the militancy of da'wah, religious identity, and spiritual capital amidst the challenges of modernity and materialist culture. Theoretical framework: This study draws on transformational pedagogy, experiential learning theory, Pierre Bourdieu's habitus theory, and the concept of spiritual capital to explain the internalization of values, the formation of religious identity, and the transformation of spiritual awareness through the practice of khuruj in Jamaah Tabligh. Literature review: This study examines the concept of khuruj as a method of da'wah within the Jamaah Tabligh, experiential pedagogy, the formation of religious habitus, and spiritual capital within the transnational Islamic movement. Method: This study uses a descriptive, qualitative approach, drawing on library research and socio-religious observations. Data were obtained through a literature review in the form of books, journals, documents of the Jamaat Tabligh, as well as observations of da'wah activities such as khuruj, jaulah, bayan, musyawarah, and communal life of the Jamaat Tabligh. Data analysis was conducted descriptively-interpretatively through theme classification, theoretical interpretation, and source triangulation. Results: The study indicates that khuruj in the Jamaat Tabligh not only serves as a method of spreading da'wah but also functions as a transformative education system that shapes members' religious character, da'wah militancy, and spiritual capital. The practice of khuruj builds spiritual discipline through the habituation of worship, material sacrifice, simplicity of life, Islamic brotherhood, and direct involvement in door-to-door da'wah. This system results in the transformation of religious identity, strengthens the sense of belonging to Religion (sense of belonging), and forms a da'wah habitus based on devotion and social service. The study also shows that the Jamaat Tabligh presents a form of spiritual resistance to the culture of materialism, individualism, and the commodification of Religion in the modern era. Implications: Khuruj becomes a model for da'i cadre formation, grounded in spiritual experience, religious habituation, and social solidarity, to strengthen the moral integrity of da'wah practitioners. Novelty: This study examines khuruj as a transformative pedagogy that shapes the habitus and spiritual capital of the Jamaat Tabligh as a form of resistance to modern materialism.